DETERMINATION OF THE COSTS ASSOCIATED WITH INHIBITION OF CARS ON HUMPS - Rohov, M. V.; Bozhko, M. P. (Science and Transport Progress, 2006)
The technique of calculation the consumptions of energy for the braking of cars on the sorting humps is offered. The existence of the braking modes with a minimum consumption of energy ensuring a executing the requirements of interval and aiming speed control of a cuts is established.